2018
DOI: 10.1007/s12053-017-9603-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the energy saving potential of anidolic system in the tropics

Abstract: Get the table of contents of every new issue published in Energy Efficiency. Please send me information on new Springer publications in Energy Policy, Economics and Management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Rightly installed on a window top part, most daylighting systems have demonstrated a great potential "to capture sunlight under clear and/or intermediate sky conditions and redirect the direct component of daylight toward the room ceiling fraction closer to the window" [13] and be a promising daylighting solution [18]. In an analysis of the impacts of light shelves in office spaces in Toronto, Canada, Berardi and Anaraki (2015) concluded that a constant increase in Window-to-Wall Ratio (WWR) reduces Useful Daylight Illuminance (UDI) of the near window area and increases UDI for the back part of the room [20].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rightly installed on a window top part, most daylighting systems have demonstrated a great potential "to capture sunlight under clear and/or intermediate sky conditions and redirect the direct component of daylight toward the room ceiling fraction closer to the window" [13] and be a promising daylighting solution [18]. In an analysis of the impacts of light shelves in office spaces in Toronto, Canada, Berardi and Anaraki (2015) concluded that a constant increase in Window-to-Wall Ratio (WWR) reduces Useful Daylight Illuminance (UDI) of the near window area and increases UDI for the back part of the room [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the current literature on the ADS pays particular attention to visual comfort but rarely thermal comfort. Therefore, a reasonable compromise between visual and thermal comfort, as well as energy consumption, becomes the main issue for energyoptimized aperture design in the tropics and subtropics [18].…”
Section: Introductionmentioning
confidence: 99%
“…This system consists of three main elements: (i) an anidolic exterior component, (ii) a false ceiling, and (iii) a twenty-one-light duct. For the AIC geometry, we referred to: reference [39] for the AIC configuration, and reference [16] for modelling a specific system for our case study based on simulations of a series of different width of the exterior aperture [13]. Moreover, another parametric study has been developed for the light duct configuration in relation to width and location on the false ceiling.…”
Section: Test Model Characteristicsmentioning
confidence: 99%
“…This peculiar condition poses additional challenges to achieve a comfortable office environment; indeed, it is a crucial element to carefully consider when defining office design strategies. It has been proved in many studies that using daylighting guide systems, especially in deep-plane spaces, contribute to: (i) naturally illuminate deep buildings, (ii) control the daylight space penetration, (iii) avoid glare and create a comfortable visual environment, and (iv) contribute effectively to the energy-saving by reducing the need for artificial lighting [13][14][15][16]. Those systems can redirect both direct and diffuse natural light to the core of the building, up to 8 m, by means of reflection, refraction, or deflection.…”
Section: Introductionmentioning
confidence: 99%
“…The manifest of those variables has the prospect of affecting building performance and can imply the mid-rise building located in the tropical climate country. It has dominantly a high intensity of solar radiation throughout the year, so even the clear sky with the diffused light has a diffuseness degree of is around 20% [7,8].…”
Section: Introductionmentioning
confidence: 99%